2015
DOI: 10.1007/s10973-015-4692-z
|View full text |Cite
|
Sign up to set email alerts
|

Thermal analysis of hydroxyapatite with adsorbed oxalic acid

Abstract: The specific adsorption of oxalic acid ions at the hydroxyapatite interface was investigated by means of the radioisotope method ( 14 C) as a function of oxalic acid ions concentration, NaCl concentration and pH. Application of hydroxyapatite has become extensive in the biomaterial field due to its biocompatibility with human hard tissue. Hydroxyapatite was synthesized using wet methods. Physical properties of the resulting powder were characterized by DTA/TG, XRD, AFM and SEM microscopy. Physicochemical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…The first weight loss of 8.3 wt.% is observed from 30 to 225 • C due to the removal of trapped water in the sample. The second weight loss of approximately 31.6 wt.% occurs from 226 to 700 • C and was attributed to the decomposition of the other components (CO 3 2− according to the weight loss observed in TGA curves between 550-950 • C [31,38]. The results obtained for the non-treated and treated specimens with carbonated hydroxyapatite solutions 0.25 g/L concentration, revealed that by brushing, acicular crystals of approximately 500 nm in length and 10 nm in width were obtained ( Figure 8); and the second one, when the solution was sprayed on the stone surface, agglomerates of spheroidal crystals of approximately 10 ± 20 nm in diameter were obtained (marked by arrows).…”
Section: Discussionmentioning
confidence: 96%
“…The first weight loss of 8.3 wt.% is observed from 30 to 225 • C due to the removal of trapped water in the sample. The second weight loss of approximately 31.6 wt.% occurs from 226 to 700 • C and was attributed to the decomposition of the other components (CO 3 2− according to the weight loss observed in TGA curves between 550-950 • C [31,38]. The results obtained for the non-treated and treated specimens with carbonated hydroxyapatite solutions 0.25 g/L concentration, revealed that by brushing, acicular crystals of approximately 500 nm in length and 10 nm in width were obtained ( Figure 8); and the second one, when the solution was sprayed on the stone surface, agglomerates of spheroidal crystals of approximately 10 ± 20 nm in diameter were obtained (marked by arrows).…”
Section: Discussionmentioning
confidence: 96%
“…What is more, the isoelectric point of the solid without the polymer is located at pH 3.4. Such big difference between pH pzc and pH iep values of activated carbon may be a result of overlapping of the electrical double layers formed on the mesopore walls [38, 39].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen in Figure 3 the isoelectric points (iep) of metal oxides without the polymer are located at pH values 6, 6.4 and 8.4 for Cr 2 O 3 , ZrO 2 and Al 2 O 3 adsorbents, respectively. Some differences between the pH pzc and pH iep values of applied oxides are a result of overlapping of the electrical double layers formed on the mesopores surface existing in the solids structure (Skwarek, 2014, 2015).
Figure 3.Values of pH iep for the metal oxide systems without and with the ionic polymer.
…”
Section: Resultsmentioning
confidence: 99%